2021
DOI: 10.3390/ani11051421
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and Subcutaneous Fatty Acid Composition and the Evaluation of Ageing Time on Meat Quality Parameters of Hispano-Bretón Horse Breed

Abstract: A full-randomized block design was used for the study of the FA composition and meat quality parameters, considering ageing time as a split-plot factor. Chemical and fatty acid composition of steaks (longissimus thoracis and lumborum muscle) from 15 month old semiextensively reared Hispano-Bretón horses were characterized (day 0), and the effect of vacuum ageing (0, 7, 14 and 21 days) on several meat quality parameters (pH, instrumental color and texture and cook loss) was determined. The average fat content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
8
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 81 publications
10
8
4
Order By: Relevance
“…However, m. pectoralis profundus has not been evaluated by any authors. WBSF decreased during aging and this is in agreement with authors [47,48] who showed lower WBSF values in different muscles after aging.…”
Section: Meat Qualitysupporting
confidence: 92%
See 1 more Smart Citation
“…However, m. pectoralis profundus has not been evaluated by any authors. WBSF decreased during aging and this is in agreement with authors [47,48] who showed lower WBSF values in different muscles after aging.…”
Section: Meat Qualitysupporting
confidence: 92%
“…Many authors who investigated the fatty acid composition of young foal meat [14,16,20,22,45,48] reported higher proportions of SFA than those found in old horse meat in the present study. Moreover, no significant differences have been found, either between males and females or between age groups.…”
Section: Fatty Acid Compositionsupporting
confidence: 52%
“…In detail, considering the majority fatty acid, C16:0, both groups presented similar amounts and corresponding to those found in 24-month female BU foals [20] and in 11-month male Italian Heavy Draught Horses (IHDH) [13]. Conversely, JN foals showed C18:0 values comparable to the contents obtained by Lorenzo et al [9] and Beldarrain et al [10] in Galician Mountain (GM) and Hispano-Bretón (HB) horse breeds, respectively. On the contrary, the BU group reported C18:0 contents less than those previously reported by other authors [18,20], who studied the same foal breed.…”
Section: Effect Of Breed and Finishing Diet On Fatty Acids Profilesupporting
confidence: 84%
“…In particular, owing to their unique digestive physiology, they are characterized by a higher intake capacity, lower methane emissions, and the ability to efficiently absorb and transfer dietary polyunsaturated fatty acids (PUFAs) (before the anaerobic microbial hydrogenation) from feed (pasture) to muscle tissues with very low deposition of trans-fatty acids [ 2 , 8 , 9 ]. Therefore, its fatty acid profile is usually described as “healthy” due to its high levels of essential and other PUFAs, such as α-linolenic (C18:3 n -3) and other long-chain fatty acids, that have been reported to have beneficial properties for preventing chronic diseases [ 2 , 10 , 11 ]. In this regard, several studies have pointed out that horses produce nutritionally valuable meat, characterized by high-value proteins, iron, B type vitamins, as well as a low fat and cholesterol amounts and a favorable dietetic fatty acids profile [ 4 , 6 , 7 , 9 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among trans FAs, reported in horse meat as 9t- and 11t-C18:1, it is known that ruminants’ meat has markedly greater CLA (conjugated linoleic acid) concentration compared to meat produced by monogastric animals [ 43 ]. For this reason, equid meat shows only trace CLA content compared to beef or lamb [ 44 ], as this study also confirms.…”
Section: Discussionmentioning
confidence: 99%